2009
DOI: 10.1074/jbc.m809012200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Equilibrium Properties of Regulatory Calcium Sensors of NCX1 Protein

Abstract: The crystal structures of the CBD1 and CBD2 domains of the Na ؉ /Ca 2؉ exchanger protein (NCX1) provided a major breakthrough in Ca 2؉ -dependent regulation of NCX1, although the dynamic aspects of the underlying molecular mechanisms are still not clear. Here we provide new experimental approaches for evaluating the kinetic and equilibrium properties of Ca 2؉ interaction with regulatory sites by using purified preparations of CBD1, CBD2, and CBD12 proteins. CBD12 binds ϳ6 Ca 2؉ ions (mol/mol), whereas the bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
111
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(122 citation statements)
references
References 51 publications
9
111
1
1
Order By: Relevance
“…4). A recent study measured Ca 2ϩ binding to purified CBD1 or CBD2 using a fluorescence-based assay and by 45 Ca 2ϩ binding (17). This study concluded that between 1.8 and 2.4 Ca 2ϩ ions bind to CBD1, whereas between 1.6 and 2.0 bind to CBD2, suggesting that the binding sites of the CBDs were only partially occupied.…”
Section: Discussionmentioning
confidence: 97%
“…4). A recent study measured Ca 2ϩ binding to purified CBD1 or CBD2 using a fluorescence-based assay and by 45 Ca 2ϩ binding (17). This study concluded that between 1.8 and 2.4 Ca 2ϩ ions bind to CBD1, whereas between 1.6 and 2.0 bind to CBD2, suggesting that the binding sites of the CBDs were only partially occupied.…”
Section: Discussionmentioning
confidence: 97%
“…Stopped-flow Experiments-Quin-2 was used in the stoppedflow experiments to monitor Ca 2ϩ off rates (16,17). In the stopped-flow machine SFM-3 (BioLogic), 150 l (syringe A) of proteins in buffer (100 mM KCl and 10 mM Bistris propane) were mixed with 150 l of buffer plus 200 -600 M Quin-2 (syringe B).…”
Section: Overexpression and Purification Of Cbd1 Cbd2 And Cbd12mentioning
confidence: 99%
“…Proteins-The DNA constructs of CBD1, CBD2, and CBD12 (AD-splice variant) were cloned into a pET23b vector and expressed in Escherichia coli Rosetta2 (DE3) competent cells (Novagen) as described (16,17). Overexpressed proteins were purified on nickel beads (Ͻ95% purity, judged by SDS-PAGE).…”
Section: Overexpression and Purification Of Cbd1 Cbd2 And Cbd12mentioning
confidence: 99%
See 2 more Smart Citations